Prostate cancer screening in the light of person-centered medicine - Santos, José Agostinho (2014)
For several years, there has been debate regarding the cost effectiveness of prostate cancer screening. In 2012 the U.S. Preventive Services Task Force (USPSTF) recommended against screening for prostate cancer, concluding that there is considerable evidence that this is not beneficial. The impact of the recommendations of USPSTF may be noted in the guidelines produced by other scientific societies. Clinicians need to know the evidence. The results of two randomized controlled trials, the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) and the European Randomized Study of Screening for Prostate Cancer (ERSPC), form the largest body of current evidence, although both have limitations. An analysis of the results of these trials shows a small reduction in prostate cancer deaths among men who were screened. The first trial showed no reduction in mortality [RR = 1.09 (0.87 to 1.36)], while the latter trial showed that the number of deaths from prostate cancer was 5 per 1000 men in the group without screening and 4 per 1000 men undergoing screening [RR = 0.79 (0.68 to 0.91)] after 11 years of follow up. There is evidence that 100 to 200 men per 1000 men screened will have a false-positive test. Most of these men will undergo prostate biopsy. A large proportion of patients with prostatic carcinomas detected by screening may be subjected to surgery, radiotherapy or androgen deprivation therapy. This article highlights the evidence against systematic screening. It proposes a holistic approach involving the individual in the discussion of the advantages and disadvantages of prostate cancer screening.